Penguatan Peran Puskesmas Darussalam dalam Mengatasi Masalah Gizi pada Ibu Menyusui Melalui Edukasi dan Pendampingan Gizi - Noeroel Arham; Ahul Ikbar; Muhammad Haikal; T.M Syifaul Qalbi; Maibon Maibon; Najaruddin Najaruddin (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Nutritional problems in breastfeeding mothers are one of the main challenges in Darussalam Health Center. This article examines the efforts and strategies implemented by Darussalam Health Center in addressing this problem, focusing on nutritional intervention programs, health education, and social and economic support. The nutritional intervention program involves providing supplementation and additional food, while health education includes counseling on balanced nutrition and healthy eating patterns. Social and economic support is provided through collaboration with local governments and NGOs, including basic food assistance and family economic empowerment programs. Collaboration with local communities, such as posyandu cadres and community leaders, also plays an important role in supporting the success of the program. The evaluation results show that effective collaboration between health workers and local communities is very important in improving the nutritional status of breastfeeding mothers. Before supplementation, the percentage of anemia (40%) and after supplementation, the percentage of anemia (25%). The data obtained show that this program has succeeded in increasing the hemoglobin levels of breastfeeding mothers and reducing the prevalence of anemia